2012
DOI: 10.7842/kigas.2012.16.6.136
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis on the Feasibility of Turbo Expander Power Generation Using Natural Gas Waste Pressure

Abstract: -Thermodynamic equations for the electric power and temperature in a turbo expander generator (TEG) using pressure energy in a natural gas line are derived. From the equations, it was shown that dominant factor is not the pressure difference but the pressure ratio. The high energy level in the inlet of TEG can be made from nearly no expense of electric energy input, which means TEG can be treated as one of newly available clean energy source. If a post heating method is chosen to heat up expanded natural gas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
(1 reference statement)
0
1
0
1
Order By: Relevance
“…[3][4][5][6][7][8][9]. In [3] it was indicated that the turbine may be an interesting alternative to the pressure reduction station.…”
Section: Figurementioning
confidence: 99%
“…[3][4][5][6][7][8][9]. In [3] it was indicated that the turbine may be an interesting alternative to the pressure reduction station.…”
Section: Figurementioning
confidence: 99%
“…현재 천 연가스의 감압에는 압력제어밸브를 사용하며 이 과 정에서 막대한 양의 압력이 버려지고 있다. 천연가 스 공급시스템을 하나의 사이클로 간주하여 보면 액 상에서 가압한 뒤 기화시킨 천연가스의 에너지를 버 리고 있는 것과 같다 [2].…”
unclassified